PRESSURELESS SINTERING OF AL2O3-SIC WHISKER COMPOSITES - KIM, YW; LEE, JG (CHAPMAN HALL LTD, 1991)
High-density compacts, up to 88% theoretical density, of Al2O3-SiC whiskers were prepared by a pressure casting and impregnation technique. Starting with these green bodies, composites of Al2O3-20 vol% SiC whiskers were pressureless sintered to higher than 95% theoretical density. They were further densified by hot isostatic pressing up to 99% theoretical density, resulting in a rupture strength of 680 MPa and a fracture toughness of 4.70 MPa m1/2.
Keywords: ALUMINA; SI3N4